Ascidian photosymbiosis: Diversity of cyanobacterial transmission during embryogenesis. Issue 1 (15th April 2014) - Hirose, Euichi; Christiaen, Lionel; Sasakura, Yasunori; Satou, Yutaka; Yasuo, Hitoyoshi
Summary Some tropical ascidians of the family Didemnidae invariably harbor cyanobacterial cells in the common cloacal cavities and/or tunic. This is the only lifelong, obligate photosymbiosis reported in chordates. Photosymbionts are transferred from the maternal colony to embryos or prehatching larvae brooded in the colonies. Here we review the diversity of modes of cyanobacterial transmission to shed a light on the evolutionary history of ascidian photosymbiosis. Ascidian species exhibit several modes of cyanobacterial transmission. In Diplosoma species, the mode is constrained phylogenetically; all photosymbiotic Diplosoma have the same mode of transmission using a unique organ known as the rastrum. In other photosymbiotic species, the mode is constrained by the distribution pattern of photosymbionts in the host colony. Species of different genera have similar modes of transmission wherein they harbor cyanobacterial cells at similar sites within colonies. Accordingly, host species of distinct lineages likely acquired similar modes of transmission convergently. Why obligate photosymbiosis was established exclusively in these didemnid ascidians remains uncertain. Ascidian photosymbiosis is discussed from the viewpoint of evolution and diversification of vertical transmission. genesis 53:121–131, 2015. © 2014 Wiley Periodicals, Inc.